Peri-Implant Health and the Knowing-Doing Gap—A Digital Survey on Procedures and Therapies - Hussain, Badra; Haugen, Håvard Jostein; Aass, Anne Merete; Sanz, Mariano; Antonoglou, Georgios N.; Bouchard, Philippe; Bozic, Darko; Eickholz, Peter; Jepsen, Karin; Jepsen, Sören; Karaca, Ebru Ozkan; Kuru, Bahar Eren; et al. (Frontiers in Dental Medicine, 2021)
Objectives: Peri-implant tissue maintenance and treatment is becoming a serious challenge in implantology. With increasing numbers of implants being placed, more cases of peri-implant mucositis and peri-implantitis is seen. A digital survey on peri-implant disease management was issued to experts in periodontology and implantology to identify the tools and procedures most commonly used today to treat peri-implant diseases and successfully manage peri-implant health. The primary aim was to assess whether there is consensus in the choice of treatment to manage peri-implant diseases and to prevent their recurrence once treated. The secondary aim was to obtain insight into future protocols and /or devices, and the research and development needed. Materials and methods: Participants in this digital survey were professionals specialising in periodontology, oral surgery, and implant dentistry. The questionnaire included both a series of closed- and open-ended questions. A total of 16 countries participated. The survey was sent by e-mail to 70 individuals, 66 received the survey and 37 of receivers responded, two of the participants were excluded due to insufficient filling of the survey. In the end 35 respondents completed the survey. Results: Respondents agree that the efficacy of mechanical and chemical decontamination of implant surfaces needs to be improved and better documented. It is a common opinion that the current remedies, mostly adapted from periodontal practices, do not provide effective and reliable clinical outcomes when treating peri-implant ailments. There is a general agreement amongst experts that regularly scheduled (3–6-month intervals) maintenance treatments are essential for maintaining peri-implant health in patients experiencing implant complications. Respondents are also concerned about unnecessary use of systemic antibiotics for managing peri-implant health. Conclusion: Regardless of agreements in parts, there was no observed consensus on the most effective treatment options for treating peri-implantitis. The experts all agree it is an urgent need for well-designed, long-term follow-up randomised and controlled clinical trials comparing interventions to provide an evidence-based strategy for peri-implant health management.